Interieur Exterieur : Living in Art : From Romantic Interior Painting to the Home Design of the Future - Breuer, Gerda; Brüderlin, Markus; Kries, Mateo; Krämer, Felix; Lütgens, Annelie; Richter, Peter; Schmidt, Petra; Tietenberg, Annette; Vitt, Andreas M.; Warnke, Martin; Wolfsburg (Wolfsburg : Kunstmuseum Wolfsburg, 2008)
Aarnio, Eero ; Armleder, John ; Artschwager, Richard ; Bacon, Francis ; Bäckström, Miriam ; Blechen, Carl ; Boullée, Etienne-Louis ; Bouroullec, Ronan ; Bouroullec, Erwan ; Breuer, Marcel ; Chalayan, Hussein ; Colette ; Demand, Thomas ; Fischl, Eric ; Fleury, Sylvie ; Friedrich, Caspar David ; Graham, Dan ; Gray, Eileen ; Grcic, Konstantin ; Gropius, Walter ; Gutzwiller, Sebastian ; Hamilton, Richard ; Heise, Almut ; Henning, Anton ; Hoffmann, Josef ; Hollein, Hans ; Hubbard, Teresa ; Birchler, Alexander ; Hummel, Johann Erdmann ; In Sook Kim ; Jacobsen, Arne ; Jones, Sarah ; Judd, Donald ; Keller, Albert von ; Kellndorfer, Veronika ; Kersting, Georg Friedrich ; Kiesler, Friedrich ; Knoebel, Imi ; Koelbl, Herlinde ; Lanzinger, Pia ; Lichtenstein, Roy ; Longo, Robert ; Loos, Adolf ; Margreiter, Dorit ; Matisse, Henri ; Merz, Mario ; Mies van der Rohe, Ludwig ; Moll, Carl ; Mondriaan, Piet ; Morrison, Jasper ; Muche, Georg ; Munch, Edvard ; Newson, Marc ; Panton, Verner ; Poliakoff, Serge ; Ranner, Alexandra ; Abele, Markus ; Reber, Nicolas ; Rehberger, Tobias ; Rockenschaub, Gerwald ; Rosler, Martha ; Schlemmer, Oskar ; Schütte, Thomas ; Shulman, Julius ; Slotawa, Florian ; Sobek, Werner ; Starck, Philippe ; Suuronen, Matti ; Thiel, Dieter ; Tischbein, Johann Heinrich Wilhelm ; Toroni, Niele ; Vallotton, Félix ; de Velde, Henry Van ; Vuillard, Edouard ; Weischer, Matthias ; Wewerka, Stefan ; Zittel, Andrea
Exhibition. Interior Exterior : Living in Art, Kunstmuseum Wolfsburg, 2008-11-29. 2009-04-13
boek